2015
DOI: 10.1038/hdy.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale landscape genetics of the American badger (Taxidea taxus): disentangling landscape effects and sampling artifacts in a poorly understood species

Abstract: Landscape genetics is a powerful tool for conservation because it identifies landscape features that are important for maintaining genetic connectivity between populations within heterogeneous landscapes. However, using landscape genetics in poorly understood species presents a number of challenges, namely, limited life history information for the focal population and spatially biased sampling. Both obstacles can reduce power in statistics, particularly in individual-based studies. In this study, we genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 85 publications
1
34
0
Order By: Relevance
“…However, we are confident of our results for a number of reasons. It has been shown that these models are robust to type I errors4142 and do not fail when using sPCA principal components as response variables4043. In addition, ρ was consistently high in our models, and the residuals showed little to no spatial autocorrelation (Table S1), indicating that these models accounted adequately for the spatial autocorrelation.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…However, we are confident of our results for a number of reasons. It has been shown that these models are robust to type I errors4142 and do not fail when using sPCA principal components as response variables4043. In addition, ρ was consistently high in our models, and the residuals showed little to no spatial autocorrelation (Table S1), indicating that these models accounted adequately for the spatial autocorrelation.…”
Section: Discussionsupporting
confidence: 51%
“…Prudence is cautioned in interpreting spatially lagged regressions because little is known about their performance when applied to landscape genetic analyses40. However, we are confident of our results for a number of reasons.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Despite their capability to move large distances, little reliable information exists about the outcome of dispersal and previous regional studies have found contrasting patterns of gene flow (Kierepka et al . ; Kierepka & Latch ). Kierepka et al .…”
Section: Introductionmentioning
confidence: 99%
“…Kierepka et al . () found panmixia whereas badgers in Wisconsin exhibited isolation by distance and a correlation between agriculture and genetic differentiation (Kierepka & Latch ).…”
Section: Introductionmentioning
confidence: 99%